Off-label use of misoprostol for labor induction in Germany: a national survey. (April 2015) - Voigt, F.; Goecke, T.W.; Najjari, L.; Pecks, U.; Maass, N.; Rath, W.
Abstract: Objective: Misoprostol is safe and effective for labor induction in viable pregnancies. Little is known about the prevalence of off-label use of misoprostol, and the reasons for using or not using misoprostol for labor induction. As such, a national survey was conducted in Germany to assess reliable data about the use of misoprostol in clinical practice. Study design: A prospective study was performed in 2013 using a standardized survey questionnaire. All registered departments of obstetrics and gynecology in Germany were targeted. Results: Out of 783 questionnaires, 542 (69%) were returned. Three hundred and fifty-five (66%) respondents reported that they use misoprostol for labor induction in viable term pregnancies, and 183 (34%) respondents reported that they never use misoprostol for this indication. The most common reasons given for using misoprostol in labor induction were: effectiveness (40%), good patient acceptance (35%), established/well proven in clinical practice (35%) and cost-effectiveness (32%). The most common reasons given for not using misoprostol were lack of licence (off-label use, 69%) and uncertainty of the legal situation (27%). Conclusion: Although misoprostol is not licensed in Germany for obstetric indications, the vast majority of respondents (66%) reported that they use misoprostol for labor induction. The main reasons for not using misoprostol for labor induction in Germany are legal concerns rather than lack of scientific evidence. Cost-effective medications with evidence-based effectiveness and safety should be supported by a clear statement from national medical societies.